Bundle of Human Resource Practices and Turnover Intentions: Mediating role of Affective Commitment in Hotel Industry, Malaysia - Beh, Loo-See; Shah, Syed Haider Ali (International Journal of Engineering and Technology, 2018)
The aim of this study is to test and propose a new framework that examines the three HR practices (motivation, empowerment and skills enhancing practices) with a mediating effect of affective commitment on turnover intentions. The novelty of this study is that it is the first study which examines the impact of three HR practices with its dimensions on turnover intentions along with the mediating effect of affective commitment. This study filled the gap and contributed by investigating the impact of such three HR practices which effect the employees’ turnover intentions in Malaysian hotel industry. Data were gathered from a managerial level employees’, with a sample of 401. In order to analyze the relationships, this study employed the structural equation modelling. Results portray that two HR practices (motivation and empowerment) are negatively associated with turnover intention while the third HR practice (Skills enhancing) is positively related with turnover intentions. The affective commitment fully mediates between Motivation and turnover intentions while, partially mediates the relationship between two HR practices (Empowerment, Skills) and turnover intentions. Thus, findings indicate that motivation and empowerment enhancing practices enhances the employees’ retentions while skills enhancing practices ought to be properly analyzed before implementing as this could be proved as counterproductive for hotels. In addition, against this backdrop the top management of hotels should devise and come up with new proper skills enhancing practices which could lead to lower down turnover intentions of employees. Replication of this study in other sectors like education or hospitals with larger sample size could extent and cross-validate the current study findings.